Fetal Growth Ultrasound in Obese Patients for the Detection of Growth Abnormalities - Martins, Juliana G.; Miller, Elizabeth; Horgan, Rebecca; Kawakita, Tetsuya (American Journal of Perinatology, 2024)
This study aimed to examine the impact of maternal obesity on fetal growth abnormalities including fetal growth restriction (FGR) and large for gestational age (LGA) fetuses.Secondary analysis from the Nulliparous Pregnancy Outcomes Study: Monitoring Mothers-to-be (nuMoM2b). The study excluded individuals with pregestational or gestational diabetes, chronic hypertension, and other major maternal medical conditions. First-trimester ultrasound was performed to establish accurate dating criteria. Ultrasound assessments were performed at 16 to 21 and 22 to 29 weeks of gestation. Our exposure was the presence of prepregnancy obesity. Our primary outcome was rates of fetal growth abnormalities identified by ultrasound, defined as FGR (estimated fetal weight [EFW] or abdominal circumference <10th percentile) or LGA (EFW >90th percentile) among obese compared with nonobese women. A secondary analysis was performed after limiting ultrasound performed from 28 to 29 weeks. To estimate adjusted relative risks (aRRs) with 95% confidence intervals (95% CIs), we used generalized linear models with Poisson distribution and log link using robust error variance, adjusting for the predefined covariates.Of 7,354 participants, 1,443 (19.6%) had prepregnancy obesity while 5,911 (80.4%) did not. Prepregnancy obesity compared with normal weight was associated with an increased risk of fetal growth abnormalities both at 16 to 21 weeks (16.0 vs. 13.2%; aRR = 1.23; 95% CI: 1.06–1.42) and 22 to 29 weeks (16.0 vs. 12.1%; aRR = 1.33; 95% CI: 1.14–1.54). Furthermore, prepregnancy obesity compared with normal weight was associated with an increased risk of LGA both at 16 to 21 weeks (12.5 vs. 10.3%; aRR = 1.24; 95% CI: 1.05–1.47) and 22 to 29 weeks (10.6 vs. 6.9%; aRR = 1.66; 95% CI: 1.38–2.01). In a secondary analysis limited to the ultrasound at 28 to 29 weeks, both fetal growth abnormalities and LGA were associated with the presence of obesity. In any of the analyses, prepregnancy obesity was not associated with FGR compared with normal weight.Maternal obesity is associated with an increased risk of fetal growth abnormalities and LGA fetuses.
Keywords: fetal growth; ultrasound; maternal obesity; large for gestational age; fetal growth restriction